2015
DOI: 10.1007/s13197-015-1801-8
|View full text |Cite
|
Sign up to set email alerts
|

Development and standardization of sorghum pasta using extrusion technology

Abstract: Extrusion cooking is a unique method for preparing pasta, which is generally produced from durum wheat semolina. However, preparation of pasta from sorghum is not practiced in India. Therefore, the present study was undertaken to develop and standardize pasta from sorghum cultivar, M35-1 and wheat semolina of 0.1 mm particle size. Sorghum and wheat semolina in different proportions (T1;S:W-50:50, T2;S:W-60:40,T3;S:W-70:30,T4; S:W-80:20, T5; S −100) were mixed with lukewarm water (40°C) in the cold extruder for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 17 publications
(13 reference statements)
6
56
0
Order By: Relevance
“…Therefore, addition of DSF, CP, MPP, and MLP up to 15%, 5%, 5%, and 3%, respectively was considered appropriate for making pasta. Similar effect of increasing CL have been reported for wheat semolina pasta containing non‐gluten ingredients such as sorghum flour (Benhur et al, ), cereal brans (Kaur et al, ), common bean flour (Gallegos‐Infante et al, ), finger millet (Gull et al, ), split pea, faba bean, white bean, yellow pea, lentil (Petitot et al, ; Wojtowicz & Moscicki, ), defatted peanut flour, and carrot powder (Badwaik et al, ).…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Therefore, addition of DSF, CP, MPP, and MLP up to 15%, 5%, 5%, and 3%, respectively was considered appropriate for making pasta. Similar effect of increasing CL have been reported for wheat semolina pasta containing non‐gluten ingredients such as sorghum flour (Benhur et al, ), cereal brans (Kaur et al, ), common bean flour (Gallegos‐Infante et al, ), finger millet (Gull et al, ), split pea, faba bean, white bean, yellow pea, lentil (Petitot et al, ; Wojtowicz & Moscicki, ), defatted peanut flour, and carrot powder (Badwaik et al, ).…”
Section: Resultssupporting
confidence: 64%
“…The drastic reduction in BD was found in DSF incorporated pasta followed by CP, MLP, and MPP pasta. Benhur et al () reported that bulk density of pasta prepared from 50:50 blend of wheat semolina and sorghum semolina (450 kg/m 3 ) was maximum compared to pasta prepared from 100% sorghum semolina (360 kg/m 3 ). While incorporation of defatted peanut flour (DPF) and carrot powder (10 g) in wheat semolina, the bulk density of pasta increased from 241.6 to 321.3 kg/m 3 with an increase in level of DPF from 8 to 22 g (Badwaik et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proximate composition of different soy okara‐supplemented pasta varied significantly ( p < .05) compared to control durum wheat semolina pasta (Table ). The control pasta had the lowest moisture content of 3.55 ± 0.01%, while for soy okara‐fortified pasta (10%–50%), it varied up to 8.26 ± 0.18%, still remained acceptable for safe storage and viability of the food products (Benhur et al, ). An increase in ash, fat, protein, and fiber contents were observed as soy okara concentrations increased in the formulation (0–50 g/100 g), whereas reverse trend was observed for carbohydrate content.…”
Section: Resultsmentioning
confidence: 99%
“…Most of these additional ingredients has focused on manipulation of glycaemic index (GI) since clinical reports have suggested that food with low GI has been directly associated with the reduced risks of hyperlipidaemia, cardiovascular diseases, extending satiety, and improved insulin sensitivity (Chillo, Ranawana, & Henry, 2011;Dona, Pages, Gilbert, & Kuchel, 2010). Researchers have developed the pasta with various bioactive ingredients such as pasta from fish material (Desai, Brennan, & Brennan, 2019;Desai et al, 2018;Parvathy, Bindu, & Joshy, 2017), mushroom powder-based pasta (Gao, Brennan, Mason, & Brennan, 2016;Lu et al, 2018), millets pasta (Gull, Prasad, & Kumar, 2015;Jalgaonkar & Jha, 2016;Kamble et al, 2019), cereal, pseudocereal, and super grain-enriched pasta (Benhur et al, 2015;Menga et al, 2017).…”
Section: Introductionmentioning
confidence: 99%